Research using teacher or teacher educator job advertisements: A scoping review - Mankki Ville (Cogent OA, Taylor & Francis Group, 2025)
Job advertisements provide accessible and practical data to explore labour market dynamics and recruitment trends. This paper presents a scoping review of empirical studies using teacher or teacher educator job advertisements as primary data. Particularly, this review will provide a structured overview of the methodology and objectives of the studies in order to gain a better understanding of how job advertisements in the fields of teaching and teacher education have been investigated, and from what perspectives. As a result of a comprehensive search strategy, which included eight database searches, Google Scholar searches and a hand-search of the citations and reference lists, a total of twenty-three studies were included for this review. The studies sought to achieve a wide range of research objectives by analysing candidate descriptions, position descriptions, and institution descriptions contained in the advertisements. By pointing out the deficiencies of existing research in its methodological rigour, such as selecting data sources, sampling and conducting analysis, this review serves as a useful guide for conducting and further developing job advertisement research in the field of education.